Utilization zingiberaceae as traditional medicinal plants in the dayak jangkang tribe community, sanggau regency - Benediktus Ege; Hendrikus Julung; Markus Iyus Supiandi; Susriyati Mahanal; Siti Zubaidah (JPBIO (Jurnal Pendidikan Biologi), 2022)
One of the plant families that are widely used as medicinal plants is Zingiberaceae. This study aims to determine the use of Zingiberaceae as traditional medicine. The method used in this study is a qualitative descriptive method with an ethical and emic approach. There are 7 families of Zingiberaceae that are used by the Dayak Jangkang tribe, namely bongah (Curcuma domesticaValeton), bongah raya hitam (Curcuma aeruginosa Roxb), bongah raya kunyit (Curcuma amada Roxb), bongah raya putih (Curcuma zedoaria Roxb), longkas (Alpinia galangal (L.) Willd), loyak joronang (Zingiberofficinale Roscoe), tabau (Kaempferia galanga L). The part used as medicine is the rhizome. Simple processing methods include mashing, boiling, drinking, mashing and smearing. The community of the Dayak Jangkang tribe uses family plants Zingiberaceae for traditional medicine hereditary. Basically, the society knows the use as medicine without knowing the chemical composition of plants Zingiberaceae family, but the community believe that its use as medicine still has to match the dose in order to get cure a disease.